Differences in motor abilities between football players of different positions - Beslija, T.; Kezic, A.; Tomljanovic, M.; Cular, D. (World Congress of Performance Analysis of Sport XII, 2018)
The purpose of this study was to determine the differences between results of motor ability tests between football players of different positions. Twenty-two first-league football players participated in this study. Variables of 20 m sprint, long jump and different measures of vertical jumps on the Optojump platform were measured. Pearson s correlation coefficient showed the greatest correlation between variables Height CMJ and T flight CMJ (r= 0,91); Height SJ and Height CMJ (r= 0,92); Height SJ and T flight CMJ (r= 0,91 and; Height DJ and T flight DJ (r=1). Significant differences between players of different positions occurred in these variables: sprint 20m and T flight CMJ. Differences also occurred between wingers and strikers in variables Height CMJ and T flight CMJ. For further research it is necessary to expand the sample with players from different clubs.